Kebijakan Redesain Sistem Perencanaan Dan Penganggaran: Implementasi Pada Pusat Pelaporan Dan Analisis Transaksi Keuangan - Mais, Rimi Gusliana; Hendra, Lim; Fathurrochman, Galih (Owner : Riset dan Jurnal Akuntansi, 2024)
Government budgeting system reform policies or in Indonesia call “Redesain Sistem Perencanaan dan Penganggaran” (RSPP) is a system initiated by the Ministry of Finance and the Ministry of National Development Planning that is effective for all ministries and institutions in 2021. RSPP aims to be a real implementation of the money follow program policy and strengthen the application of performance-based budgeting. This research aims to analyse the implementation of RSPP, along with its constraints and impacts. This research used a qualitative research method using a case study approach by interviewing 4 informants. This research was conducted at one of the state institutions, namely the Indonesian Financial Transaction Reports and Analysis Center (INTRAC). Data collection is carried out in a natural setting, primary data sources, and data collection techniques are more on direct observation, and interviews. From the analysis conducted by researchers, the implementation of INTRAC budgeting in 2023, which was carried out in 2022, is in accordance with the RSPP based on the Joint Circular Letter of the Minister of Finance and the Ministry of National Development Planning. This has an impact on budget documents that are easier to understand, and more visible activities and outputs produced by INTRAC. RSPP makes it easier for leaders to carry out monitoring, evaluation and increase effectiveness and efficiency in government budgeting.